Bidirectional microfluidic pumping using an array of magnetic Janus microspheres rotating around magnetic disks1. Issue 13 (7th July 2015) - van den Beld, Wesley T. E.; Cadena, Natalia L.; Bomer, Johan; de Weerd, Eddy L.; Abelmann, Leon; van den Berg, Albert; Eijkel, Jan C. T.
<x xml:space="preserve">Abstract</x> The presented magnetically actuated pump allows for highly localized flow control in a closed microfluidic channel.